Clinical instrumentation for the intra-operative mapping of ventricular arrhythmias. - Parson I; Downar E (Pacing & Clinical Electrophysiology, 1984)
Surgical treatment of ventricular arrhythmias has been greatly facilitated by intra-operative mapping. Present clinical mapping techniques are time-consuming, of limited accuracy, and are restricted to monoform sustained tachycardias. A previously reported on-line cardiac mapping system used in the research laboratory has been modified to provide epicardial maps of ventricular arrhythmias induced at the time of surgery. Changes such as a battery-operated multiplexer, patient electrical isolation, adjustable electrogram gain, time-code labeling and marker-matrix display, have all contributed to the intra-operative application of the original analog real-time mapping technique. These modifications were accomplished without compromising the spatial or temporal resolution (0.5 cm and 8.3 ms) of the laboratory system. An advantage of the present system is a decrease in cardiopulmonary bypass time as a direct result of the instantaneous analysis and display of epicardial activation information. In addition, it enables, for the first time, short salvos and polymorphic runs of ventricular tachycardia to be mapped intra-operatively.